In Search of Meaning in Context: Bartok’s Duke Bluebeard’s Castle - Judit Frigyesi (Current Musicology, 2000)
An understanding of Duke Bluebeard’s Castle entails two interrelated topics, which cannot be fully explored in the limited scope of this article. The first, the interpretation of the symbolism of the opera, would necessitate a thorough analysis of text and music and also the exploration of the cultural context in depth. The second topic, the definition of a “meaningful context” in relation to the symbolic world of a musical piece, is even more problematic. Even if one were instantly convinced of the existence of an inherent relationship between Lukacs’s aesthetic theory and Bartok’s music, the problem remains of how to substantiate such an “insight” in the absence of demonstrable, concrete influences. In Bartok’s case, this latter question concerns not only his relation to Lukacs, but also his cultural environment at large. We will encounter the same situation when attempting to find parallels to Bartok’s works in the poems of Endre Ady. While the meaning of influence is fairly straightforward in certain musical-technical aspects of Bartok’s style, his global aesthetic concepts in relation to his cultural environment resist concretization. In attempting, on the one hand, to explore the basic symbolic ideas of the opera, and, on the other, to address the problem of finding the context that substantiates these symbols, my conclusions will necessarily remain fragmentary.